2018
DOI: 10.17755/esosder.306839
|View full text |Cite
|
Sign up to set email alerts
|

Pedagoji̇k Formasyon Serti̇fi̇ka Programinin Değerlendi̇ri̇lmesi̇

Abstract: Bu araştırmanın amacı, pedagojik formasyon sertifika programının niteliği ve programda karşılaşılan sorunlar hakkında öğrenci ve sorumlu öğretim üyelerinin görüşlerinin ve olası politika önerilerinin belirlenmesidir. Araştırma karma desendedir. Araştırmanın nicel katılımcı grubunu pedagojik formasyon eğitimi alan 189 kişi oluşturmaktadır. Nitel boyutunda ise, katılımcı grubu 5 pedagojik formasyon öğrencisi ve pedagojik formasyon sertifika programında eğitim veren 3 öğretim üyesinden oluşmaktadır. Araştırmanın … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 7 publications
0
15
0
4
Order By: Relevance
“…Dalkılıç et al, Yıldırım and Vural, and Sever found in their studies that students who receive pedagogical formation education feel themselves more motivated towards the teaching profession because of the pedagogical education they are receiving. Altınkurt et al, Kiraz, and Dursun found out that pedagogical formation students think they will be successful in the teaching profession with the education they received and Bal found out students developed a positive attitude towards the teaching profession with this education [1,7,[53][54][55][56][57][58][59][60][61].…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Dalkılıç et al, Yıldırım and Vural, and Sever found in their studies that students who receive pedagogical formation education feel themselves more motivated towards the teaching profession because of the pedagogical education they are receiving. Altınkurt et al, Kiraz, and Dursun found out that pedagogical formation students think they will be successful in the teaching profession with the education they received and Bal found out students developed a positive attitude towards the teaching profession with this education [1,7,[53][54][55][56][57][58][59][60][61].…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…The curriculum is implemented in different ways at different universities; some universities offer this programme via face-to-face education either during the week or at weekends, while others offer this programme via distance learning. In recent years, the number of universities incorporating this programme and the quotas allocated to it have increased (Gurol, Türkan & Som, 2018;Türkkan, Uyar & Yolcu, 2017). The extent to which this programme, which provides pedagogical training to graduates from outside education faculties in a short time, achieves its goals and produces qualified teachers is constantly debated (Azar, 2011;Köse, 2017;Yüksel, 2004;Yılmaz, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which this programme, which provides pedagogical training to graduates from outside education faculties in a short time, achieves its goals and produces qualified teachers is constantly debated (Azar, 2011;Köse, 2017;Yüksel, 2004;Yılmaz, 2015). The attempt to deliver teacher training, which is normally acquired over a long period of four years in education faculties, in a short time constitutes an important obstacle to the training of qualified teachers and is accompanied by a number of problems (Gurol, Türkan & Som, 2018;Köse, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations